The association between aggregate index of systemic inflammation and DXA-measured body composition parameters in adolescents - Wang, Haihua; Tao, Luping; Zhu, Zhongxin (Frontiers in Physiology, 2025)
BackgroundSystemic inflammation during adolescence may critically influence metabolic and musculoskeletal health, yet comprehensive biomarkers predicting adverse body composition remain underexplored. The aggregate index of systemic inflammation (AISI), integrating neutrophils, platelets, monocytes, and lymphocytes, offers a novel metric to assess this relationship.MethodsThis cross-sectional study analyzed 3,661 adolescents (aged 12–19 years) from NHANES 2011–2018. AISI was calculated from complete blood counts, and body composition parameters—appendicular lean mass index (ALMI), visceral adipose tissue area (VATA), and total bone mineral density (BMD)—were measured via dual-energy X-ray absorptiometry (DXA). Multivariable linear regression and threshold effect models evaluated associations, adjusting for demographic, metabolic, and lifestyle covariates.ResultsHigher logAISI was associated with lower ALMI (β = −0.189, 95% CI: −0.262 to −0.116), greater VATA (β = 3.017, 1.266–4.769), and reduced BMD (β = −0.017, −0.027 to −0.007). A threshold effect emerged at logAISI = 2.2, beyond which inflammation’s impact on VATA and BMD intensified.ConclusionElevated AISI correlates with adverse body composition in adolescents. The identified threshold suggests a potential clinical benchmark for early intervention. These findings underscore systemic inflammation as a modifiable target to mitigate metabolic and musculoskeletal risks during this critical developmental period.